Metode Pemesanan Multi-Item Inventory dengan Pertimbangan Masa Kedaluwarsa, Unit Diskon, dan Kapasitas Gudang di Pin'kan Bakery - Daniel Reynald Budiman; I Gede Agus Widyadana (Jurnal Titra, 2018)
Inventory is the thing to consider in ordering. Inventories have a variety of properties, one of which is a level of decline. Many researchers have done research on multi-item inventory but not with inventory are deteriorating and assume constant demand. The real condition that occurs today is that the company sells multi-item inventory in the presence of stochastic deterioration and demand. The situation is approached by building a model of inventory simulation using real data in Pin'kan Bakery. The simulation model is done with the help of monte carlod simulation and evolutionary algorithm. This study will compare two ordering modes, namely continuous review and periodic review. The results show that the continuous review method is an appropriate ordering method for multi-item inventory ordering with stochastic degrees and demand.